Project Report on Design of Traffic Signal for Intersection of Platform Road Sampige Road and S C Road - BASANTA DEVKOTE, BHUPENDRA KUMAR RAI, BHUPENDRA MAN JOSHI, MAHENDRA PRASAD and SUJIT MAN RAJBHANDARI (1993)
INTERNAL GUIDE:SHIVAPRAKASH C K, MVJCE
Keywords: Platform Road Sampige Road and S C Road